Assessment of the Nutritional Composition, Microbiological and Sensory Attributes of Maize-based fortified food with Peanut and Carrot Blends (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This research assessed the nutritional composition, microbiological and sensory attributes of maize-based fortified food with peanut and carrot blends. A total of six composite flour samples were formulated using varying ratios of maize, peanut, and carrot: (MPC1) 100% maize flour (control), (MPC2) 90% maize, 5% peanut, and 5% carrot, (MPC3) 80% maize, 15% peanut, and 5% carrot, (MPC4) 70% maize, 20% peanut, and 10% carrot, (MPC5) 60% maize, 25% peanut, and 15% carrot, and (MPC6) 50% maize, 30% peanut, and 20% carrot. The proximate, mineral, vitamin, antinutrient, and functional properties of these fortified food samples were assessed using established methodologies. The proximate analysis revealed a significant increase (p